Defluoridation of Drinking Water using Brick Powder as an Adsorbent - Singh, Renu; Raghuvanshi, Shiv Pratap; Kaushik, C.P. (Asian Journal of Chemistry, 2010)
Kinetics study in batch process to understand the feasibility and effectiveness of adsorbents brick powder were applied on aqueous samples prepared in laboratory and groundwater samples of higher fluoride concentration collected from two villages, namely Hussainpur and Thodwal of Haryana, India. Different parameters, for instance, effect of pH, effect of dose and contact time of adsorbent were studied and optimized. For the optimum condition i.e., pH (6-8) and dose of adsorbents (0.6-1.0 g/100 mL), the percentage of defluoridation from aqueous (synthetic) sample, was found to be increase from 29.8 to 54.4 % for brick powder and 47.6-80.4 % for chemically activated carbon (CAC) with the increase in contact time of 15 to 120 min. Fluoride removal was found to be 48.73 and 56.4 % from goundwater samples having 3.14 and 1.21 mg/L fluoiride, respectively under the optimized conditions. Defluoridation capacity of brick powder can be explained on the basis of the chemical interaction of fluoride with the metal oxides under suitable pH conditions.